2007
DOI: 10.3201/eid1311.061461
|View full text |Cite
|
Sign up to set email alerts
|

Possible Typhoon-related Melioidosis Epidemic, Taiwan, 2005

Abstract: LETTERSsequencing. This infection rate is within the range (13.5%-90%) that has been reported for R. felis infecting Ctenocephalides fl eas in Brazil and Uruguay (2,3,7). Sixteen (72.7%) cats contained R. felis-reactive antibodies; 4 of them showed titers to R. felis at least 4-fold higher than those to the other 5 rickettsial strains, fi ndings that enabled us to technically conclude that these cats were exposed to R. felis or a closely related organism (1,7,9). Our fi nding of 70% R. felis infection in fl ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…We found that typhoon was positively correlated with ambient B. pseudomallei . This supports conclusions from previous studies that the case clusters were associated with sudden and heavy rainfall related to cyclones and typhoons [1], [4], [6], [10], [14][18], [22]. Wind speed was reversely correlated with ambient B. pseudomallei .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that typhoon was positively correlated with ambient B. pseudomallei . This supports conclusions from previous studies that the case clusters were associated with sudden and heavy rainfall related to cyclones and typhoons [1], [4], [6], [10], [14][18], [22]. Wind speed was reversely correlated with ambient B. pseudomallei .…”
Section: Discussionsupporting
confidence: 91%
“…However, pneumonia was the most common clinical presentation, which accounted for 32.6%, 51%, 45%, 42.1% and 70% of cases in India [5], northern Australia [10], Thailand [1], Malaysia [15], and Taiwan [14], respectively. In addition, epidemiological studies hypothesized that inhalation of B. pseudomallei was the mode of transmission after heavy monsoonal rains and winds [5], [6], [10], [13], [17], [20][22]. In this study, we successfully quantified ambient B. pseudomallei using filtration/real-time qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cases were categorized as being acquired during prior travels to areas of endemicity overseas rather than by indigenous acquisition, because the confirmed cases were rare and the pathogens were never isolated from the environment. However, the number of melioidosis cases suddenly increased in the Er-Ren River Basin in southern Taiwan after a typhoon followed by a flood in 2005 (8,9). B. pseudomallei was isolated from agricultural crop soil, and the prevalence of B. pseudomallei-specific antibodies increased significantly among residents after the typhoon and flood incident (9).…”
mentioning
confidence: 99%